The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/13676261.2017.1333585
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and alcohol in young adolescence: the perceived difference between youthful and adult drinking

Abstract: This paper examines the evolving social identities of young adolescents in regard to alcohol and drinking culture in Norway. Detailed analysis of 29 focus group interviews and 32 individual interviews with 12-13-year-olds reveal a thorough negative attitude towards alcohol, especially when enjoyed by young people. Young adolescents found young people to be too irresponsible and immature to drink, while adults were portrayed as capable of enjoying alcohol without losing control or experiencing other negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…This notion is based on age group and its related developmental stage, which relates to identity crisis and identity formation (see Erikson, 1956). Prior research on social identity also showed these age groups as participants (Bakken, Sandøy, & Sandberg, 2017;Benson & Elder, 2011;Crocetti & Rubini, 2017;Crocetti, Sica, Schwartz, Serafini, & Meeus, 2013). These studies centered on external variables such as psychosocial maturity, age The decision of the context where the research would be done also needs to be made.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is based on age group and its related developmental stage, which relates to identity crisis and identity formation (see Erikson, 1956). Prior research on social identity also showed these age groups as participants (Bakken, Sandøy, & Sandberg, 2017;Benson & Elder, 2011;Crocetti & Rubini, 2017;Crocetti, Sica, Schwartz, Serafini, & Meeus, 2013). These studies centered on external variables such as psychosocial maturity, age The decision of the context where the research would be done also needs to be made.…”
Section: Introductionmentioning
confidence: 99%
“…In working with boundaries, we can also study how participants rationalize particular behavior in certain situations, creating situated legitimacy. Bakken, Sandøy, and Sandberg (2017) show how boundary work is a fruitful way of trying to understand young people's relationships with alcohol and adulthood. In their study, they analyze how young adolescents (12-13 years) perceive differences in youthful and adult drinking, and conclude that comparisons to other social groups function as a way of presenting themselves as mature.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research also points to young people over time becoming more focused on 'sensible' drinking within reasonable limits than on excessive drinking which includes loss of control (Kloep et al 2001), that an ideal of conscientiousness is important in young people's relation to alcohol (e.g. Bogren 2006), and that control is central in descriptions of legitimate alcohol use (Bakken, Sandøy, and Sandberg 2017). Generally, this period in life can be viewed as a time of emerging adulthood; a time when young people seem to have left adolescence but without having completely accepted and moved into adulthood (Arnett 2000;MacMillan 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They believed that young people drink because they want to be cool, because they are miserable, or because of group pressure. These narratives were interpreted as reflecting a deep-rooted cultural ambivalence towards alcohol use in Norway while also suggesting that boundaries between ‘adolescents’ and ‘adults’ are fundamental when understanding emerging adolescent social identities, especially when it comes to drinking and drinking culture 58…”
Section: Findings To Datementioning
confidence: 99%
“…These questions will be examined both quantitatively (ie, examination of adolescents’ repeated surveys, parental surveys and various administrative data sources) and qualitatively (ie, examination of adolescents’ repeated individual and group-based interviews using thematic content and narrative analyses). Further, we aim to both quantitatively and qualitatively explore numerous understudied and emerging questions, including the problematic use of social media and video games,49–52 the role of alcohol and drug use opportunities,39 42 53 putative gender, ethnic and socioeconomic variations and differences,15 54 55 resilient outcomes in face of multiple risk factors41 and shifting cultural norms and behaviours surrounding early substance use 45 56–59. Finally, a wider range of research questions and outcomes extending beyond adolescence can eventually be addressed through various secondary projects and the planned individual-level linkages of quantitative data with other administrative and health data sources readily available in Norway 60.…”
Section: Introductionmentioning
confidence: 99%